The University of British Columbia. Issue 2 (14th June 2013) - Klein, Michael C.
Abstract This study is one of a series of recent publications that attempt to sort out the impact of mode of birth on maternal and newborn outcome. The focus on elective cesarean section compared to planned vaginal birth beginning in spontaneous labor is an improved methodology over the earlier comparisons that failed to be able to separate planned from unplanned cesarean section or vaginal birth. The retrospective case control methodology based on birth record data that is employed in this research is similar to others, though with more respectable numbers. Most suffer from the problem of ascertainment difficulties, failure to stratify by parity, and of course, the unavailability of randomization, which some consider the ideal methodology. (BIRTH 40:2 June 2013)